Population Genomics and Haplotype Analysis in Bread Wheat Identify a Gene Regulating Glume Pubescence - Hu, Xin; Zuo, Jianfang (Frontiers in Plant Science, 2022)
Glume hairiness or pubescence is an important morphological trait with high heritability to distinguish/characterize wheat, and is related to the resistance to biotic and abiotic stresses. Hg1 (formerly named Hg) on chromosome arm 1AS controlled glume hairiness in wheat. Its genetic analysis and mapping have been widely studied, yet more useful and accurate information for fine mapping of Hg1 and identification of candidate gene is lacking. The cloning of this gene has not yet been reported for the large complex wheat genome. Here, we performed a GWAS between SNP markers and glume pubescence (Gp) in a wheat population with 352 lines, and further demonstrated the gene expression and haplotype analysis approach for isolating the Hg1 gene. One gene, TraesCSU02G143200 (TaELD1-1A), encoding Glycosyltransferase-like ELD1/KOBITO 1, was identified as the most promising candidate gene of Hg1. The gene annotation, expression pattern, function SNP variation, haplotype analysis and co-expression analysis in floral organ (spike) development indicated that it is likely to be involved in the regulation of glume pubescence. Our study demonstrates the importance of high-quality reference genomes and annotation information, as well as bioinformatics analysis for gene cloning in wheat.